A Chronological Overview of the Psychology of Religion - Hood Jr, Ralph W; Spilka, Bernard (Religious Studies and Theology, 2013)
We present a chronological overview of the history of psychology of religion. The focus is upon American psychology with an emphasis on a scientific model informed by measurement and to a lesser extent experimental methods. The rise and fall of the psychology of religion is documented as is the re-emergence that began in the 1960’s and continues today. We also briefly document the psychology of religion in various European countries. Space limitations force us to explore the history of the psychology of religion primarily in chronological terms. A broader history would necessarily include in depth exploration of major figures in the history of the psychology of religion in countries other than America and Europe and focus upon various assumptions of method and procedure that define the diversity of approaches to the psychology of religion throughout history.